Robotics as a Possibility for Exploring Laterality in Early Childhood Education - Pereira, Jéssica M.; Oliveira, Ruana M. S.; Andrade, Samara C. F.; Romulo, Thaymara C. S.; Santos, Silvana C.; Faria, Rejane W. S. C.; Brandão, Alexandre S. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
In the realm of education, the utilization of diverse methodologies and resources can greatly enhance teaching and learning processes. As such, introducing robotics into early childhood education holds the potential to familiarize children with emerging technologies and bridge the gap between their daily experiences and the undeniable presence of robots in various fields. Moreover, robots offer the opportunity to create an engaging, enjoyable, and inquisitive learning environment, fostering positive experiences for children. This study aimed to explore the implementation of educational robotics as a catalyst for developing laterality skills in early childhood education. To achieve this objective, a two-hour visit was conducted at the Human Development Laboratory (LDH), an educational public institution affiliated with Universidade Federal de Viçosa (UFV), which caters for 5 to 6-year-old children. During the visit, a robot named Cowbot, chosen for its distinctive appearance, was introduced. A three-step activity was carried out, involving an assessment of children’s prior knowledge, a robot presentation, and children exploring the robot through an accompanying application. The interaction between the robot and the target audience was observed, revealing that children engaged with the robot both in an exploratory and directed manner. Preliminary results indicate positive and satisfactory outcomes, as students actively interacted with the robot, prompting curiosity and facilitating the development of laterality and programming concepts. Although the Cowbot project is ongoing, the findings from this study are expected to shed light on the potential benefits of incorporating educational robots as instructional resources in early childhood education, contributing to the development of curriculum-based skills and broader learning objectives.